Karakteristik Pergerakan Kendaraan Bermotor Di Dki Jakarta - Maimunah, Siti (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
vehicles. DK! Jakarta as a center of business and government result in the movement of vehiclesduring the dmj can reach twia! at night. The purpose of the study is to characterize the movement ofmotorized vehicles iri Jakarta, so it can re used as input in the transportation planning in Jakarta in thefuture. A suruetj was condUcted at 9 gas stations in_ Cililitan, Daan Mogot, · Karang Tengah, KelapaGading, Bekasi, Margonda, East Jakarta, Pramuka and Warung Jambu Bogar. Based on surveydata, the analysis .shaws that 694 or about 42% is a movement in Jakarta. Number of vehicles mostminibuses are the h;pes of vehicles which mm;e in. the Jakarta area that is equal. to 57.35% and theaverage number of f